Supporting the future of medicine: Student mental health services in medical school - Hale, Elijah W.; Davis, Rachel A. (Frontiers in Health Services, 2023)
Background: Mental health issues are common among US medical students, and the AAMC has established recommendations for student mental health services provided by medical schools. Few studies directly compare mental health services at medical schools across the United States and, to our knowledge, none analyze how well schools adhere to the established AAMC recommendations. Objective: To determine whether mental health services at US medical schools adhere to established guidelines. ​Methods: From October 2021 to March 2022, we obtained student handbooks and policy manuals from 77% of the accredited LCME US medical schools. The AAMC guidelines were operationalized and placed into a rubric format. Each set of handbooks was independently scored against this rubric. A total of 120 handbooks were scored and the results were compiled. ​Results: Rates of comprehensive adherence were very low, with only 13.3% of schools displaying adherence to the full set of AAMC guidelines. Partial adherence was higher, with 46.7% of schools meeting at least one of three guidelines. Portions of guidelines whose requirements reflected a standard for LCME accreditation displayed a higher rate of adherence. ​Conclusion: The low rates of adherence across medical schools, as measured by handbooks and Policies & Procedures manuals, represents an opportunity to improve the mental health services within US allopathic schools. An increase in adherence could be a step towards improving the mental health of US medical students.